Penanaman Nilai-Nilai Karakter dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Anggi Rahmanida Nst; Aisyah Rizqa Fitri Siregar; Edi Syaputra (Universitas Dehasen Bengkulu, 2022)
Indonesian language learning has an important role in shaping students' habits, attitudes, and abilities for the next stage of development. In addition, learning must be able to help students develop language skills in their environment, not only to communicate, but also to absorb various values and knowledge that are assessed. The importance of Indonesian language lessons for elementary school (SD) students is directed at increasing the ability of students to be able to communicate in Indonesian properly and correctly, both orally and in writing, as well as fostering an appreciation of the literary works of the Indonesian nation. With this basis, a teacher must realize that learning Indonesian is learning about language skills, not learning about grammar.